The effectiveness of piper betel solution and combination of sodium hypochlorite and hydrogen peroxide in root canal irrigation for endodontic treatment: A scanning electron microscope study. - Etty Indriati, Etty Indriati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Root canal irrigation is a step needed in endodontic treatment, after extirpation of dental nerves, to clean the debris in the root canal in infected tooth pulp. The cleaned root canal was then filled with synthetic nerves and thus allowed the tooth crown to be preserved and function normally in the oral cavity.Objective: This study was aimed to compare the effectiveness of piper betel solution with the combination of sodium hypochlorite and hydrogen peroxide as irrigation material in dental root canal treatment. Material and Method: The material of study consisted of 6 upper incisors that were sectioned longitudinally into 12 parts. This study used in vitro method, by applying standard root canal treatment: preparation, extirpation, and irrigation of the root canal of incisor teeth. After irrigation (one group of teeth used piper betel solution; and the other group used combination of sodium hypochlorite and hydrogen peroxide), the tooth was longitudinally cut becoming mesial and distal parts. These parts were examined under scanning electron microscope with 500 magnification, and photographed using electron micrograph on the apical, middle, and coronal sections. The amount of debris was calculated (pm2) in each of those sections.Results: Irrigation using piper betel solution showed less amount of debris (n = 12, mean = 565 pm2) in the root canal, compared to combination of sodium hypochlorite and hydrogen peroxide (n = 12, mean =703,um2). However, the t test statistical analysis showed no significant difference between the two.Conclusion: Because of the toxicity of combination of sodium hypochlorite and hydrogen peroxide, no significant difference in irrigation material for root canal treatment, and the cleaner effect of piper betel solution, I suggest piper betel solution to be used widely as irrigant in endodontic treatment.Key words: root canal, piper betel, sodiumÂ hypochlorite, hydrogen peroxide, incisor teeth